The Implementation of Resource Based Learning of Material Funeral Management at MA Ma'arif Roudlotut Tholibin Metro Class X - Sari, Irma Yuliana; Aziz Q, Ikhwan; Ehwanudin, Ehwanudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Resource-based learning is an educational approach that captivates students by providing a novel atmosphere, thereby enhancing their motivation throughout the learning process. This study aims to elucidate the implementation of resource-based learning concerning the management of corpses at Ma Ma'arif Roudhlotut Tholibin in Metro City, specifically in Class X, while examining the method's execution and its impact on students' engagement with resource-based learning. This research adopts a qualitative methodology, employing data collection techniques such as observation, interviews, and documentation. The study subjects include the head of the madrasah, the Fiqh subject teacher, and the students of Class X at Ma Ma'arif Roudhlotut Tholibin Metro. The validity of the data is ensured through triangulation, while data analysis involves reduction, conclusion drawing, and presentation. The findings indicate that during the corpse management lessons, the instructor employs the RBL learning method, utilising resources such as the school environment, textbooks, videos, and various teaching aids. This approach fosters student enthusiasm and cultivates a conducive learning atmosphere. Consequently, Fiqh teachers engaged in resource-based learning can effectively motivate students, creating an engaging environment that facilitates a comprehensive understanding of corpse management principles.